Pengaruh Hybrid Work Model terhadap Budaya Kerja - Rhamzy Fadhil Fauzan; Sri Suwarsi (Bandung Conference Series: Business and Management, 2023)
Abstract. A good work system is a system that can be mutually beneficial, both to employees and to the company itself. The work system is a series of certain patterns in carrying out a field of work which is very important in its implementation to achieve the company's vision and mission, it also requires a good work culture. The occurrence of covid 19 made the work system have to adapt to circumstances in the interest of health, therefore the WFH system was born during the covid period. However, after the pandemic subsided, the company found a work system that can benefit both parties, namely Hybrid, where the company provides a new work system adapted from (Work From Home) and (Work From Office) in the New Normal era. This research explains (i) how the implementation of the hybrid work system is carried out by KOMINFO (ii) knows how the work culture is and (iii) whether there is an influence of the Hybrid Work Model on work culture. The research uses descriptive and verification methods, with a quantitative research approach and operates the calculations using the IBM SPSS program. Data collection was obtained through, questionnaires and observation. The sampling technique is saturated sampling. Respondents in this study were KOMINFO employees of the planning division and 1000 startups totaling 50 employees. The results of this study concluded that: 1) The implementation of the hybrid work model was included in the very good category. 2) A good work culture produces changes in the way of work, interactions, and influencing norms in the organization. There is a significant influence between the Hybrid Work Model variable on the Work Culture of Ministry of Communication and Information Technology employees. Abstrak. Sistem kerja yang baik adalah sistem yang dapat saling menguntungkan, baik ke karyawan maupun ke perusahaan itu sendiri. Sistem kerja merupakan rangkaian pola tertentu dalam melaksanakan suatu bidang pekerjaan yang sangat penting dalam pelaksanaannya untuk mencapai visi dan misi perusahaan, diperlukan juga budaya kerja yang baik. Terjadinya covid 19 membuat sistem kerja harus beradaptasi terhadap keadaan demi kepentingan kesehatan, maka dari itu terlahirlah sistem WFH pada masa covid. Akan tetapi setelah meredanya pandemi, perusahaan menemukan sistem kerja yang dimana bisa menguntungkan kebelah dua pihak yaitu Hybrid yang dimana perusahaan memberikan sistem kerja baru yang di adaptasi dari (Work From Home) dan (Work From Office) di era New Normal. Riset ini menjelasakan (i) bagaimana pelaksanaan sistem kerja hybrid yang dilakukan oleh KOMINFO (ii) mengetahui bagaimana budaya kerja dan (iii) apakah terdapat pengaruh Hybrid Work Model terhadap budaya kerja. Penelitian menggunakan metode deskritif dan verifikatif, dengan pendekatan penelitian kuantitatif dan mengoperasikan perhitunganya menggunakan progam IBM SPSS. Pengumpulan data diperoleh melalui kuesioner dan observasi. Teknik penarikan sampel adalah sampling jenuh. Responden dalam penelitian ini adalah karyawan KOMINFO Divsi perencanaan dan 1000 Startup berjumlah 50 karyawan. Hasil Penelitian ini menyimpulkan bahwa : 1) Pelaksanaan hybrid work model yang dilakukan termasuk kedalam kategori sangat baik. 2) Budaya kerja yang baik menghasilkan perubahan dalam cara kerja, interaksi, dan norma yang mempengaruhi di organisasi. Terdapat pengaruh yang signifikan antara variabel Hybrid Work Model terhadap Budaya Kerja di karyawan Kementrian Komunikasi dan Informatika.